1989
DOI: 10.1070/sm1989v062n01abeh003240
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Behavior of Automorphisms of Graphs

Abstract: Electron heating (AT e /T e <30%, An e /n e < 100%) was produced in tokamak-like discharges (n e =2X 10 n cm" 3 , T e s 15 eV, n e /nH° = 20%) in the General Atomic Octopole by application of lower hybrid wave power. The heating efficiency was 50% for v^/vj = 1.7 and 17% for V0/v T = 3.4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Then, for an arbitrary finitely generated group G, the intersection, by all nonprincipal ultrafilters U on , of kernels of the homomorphisms l R U contains o G . It can be deduced from Theorem and Remark 1 of [4] that this intersection and o G coincide for any finitely generated group G if and only if there exists a positive integer c such that r i+1 < cr i for all i ∈ .…”
Section: Final Commentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Then, for an arbitrary finitely generated group G, the intersection, by all nonprincipal ultrafilters U on , of kernels of the homomorphisms l R U contains o G . It can be deduced from Theorem and Remark 1 of [4] that this intersection and o G coincide for any finitely generated group G if and only if there exists a positive integer c such that r i+1 < cr i for all i ∈ .…”
Section: Final Commentsmentioning
confidence: 95%
“…By Proposition 3.1, for any nonprincipal ultrafilter U on , there exists a countable set R j j ∈ of positive infinite elements of the corresponding nonstandard extension * of such that j∈ ker l R j = o G (Moreover, by the proof of Proposition 3.1, we can take R j = i → r i j /U where r i j ∈ and r i+1 j > r i j for all i j ∈ .) At the same time, it can be deduced from Theorem and Remark 1 of [4] that, for any ultrafilter U, the set R j j ∈ cannot be chosen independently of G.…”
Section: Final Commentsmentioning
confidence: 96%
See 1 more Smart Citation
“…The nature of the functions realized as ~r,~(g, • ) for connected locally finite vertexsymmetric graphs F, x E V(F), and g E Aut F is studied in [1]. b) either f(n) >>.…”
Section: Description Of the Possible Behaviour Of The Functionmentioning
confidence: 99%
“…In fact, it can be shown that the intersection of the kernels of these representations coincides with the subgroup o(Aut F) considered there. In turn the research conducted in [1] on the asymptotic behavior of automorphisms of graphs has enabled us to give a positive answer to the question of van den Dries and Wilkie.…”
Section: Spaces Associated With Graphs and The Van Den Dries-wukie Qumentioning
confidence: 99%